Small Molecules in the Management of Psoriasis and Psoriatic Arthritis - Venkata Chalam Konakanchi; Bikash R. Kar; Dharshini Sathishkumar; Sushil Tahiliani; Anchala Parthasarathi; Shekhar Neema; Satyaki Ganguly; Shrichand G. Parasramani; Haritha Komeravelli; Jayakar Thomas (Wolters Kluwer Medknow Publications, 2024)
Psoriasis is a common chronic, immune-mediated inflammatory skin disease associated with various comorbidities. Managing psoriasis is often challenging as the therapy is decided based on the area of the disease, associated comorbidities and impairment in quality of life, besides the patient's preference. Making progress in the development of new molecules that can be used topically or orally, effectively controlling the disease with minimal side effects and providing long-lasting remissions are the needs of the hour. Recent developments in understanding the complexities of the pathogenesis of psoriasis have resulted in the reinforcement of treatment modalities, leading to the evolution of various biologics and small-molecule inhibitors. In comparison with biologics, both patients and treating physicians prefer small molecules for various reasons such as avoiding injections and side effects that are associated with biologics biologics. Moreover small molecules are economical than biologics. Newer small molecules, both topical and oral, are promising additions to the therapeutic arsenal in the management of psoriasis in the future.